Influence of Strategic Contingency Factors on Performance of Large Manufacturing Firms in Kenya - Kihara, Dr. Allan Samuel Njogu; Ngugi, Dr. Patrick Karanja; Ogollah, Dr. Kennedy (European Journal of Business and Strategic Management, 2016)
Purpose: The main purpose of this study was to establish the influence of strategic contingency factors on performance of large manufacturing firms in Kenya by reviewing organizational structure, information technology, dynamic capabilities and leadership characteristics as the study variables with legal and regulatory environment as the moderating variable. Methodology: The study adopted a cross-sectional research design and descriptive survey design and the research philosophy was positivism. The study population study was 499 large scale manufacturing firms where a sample size of 217 firms was selected. Data was collected through the administration of questionnaires to operations managers. Results: The study findings revealed that organization structure has a significant influence on performance of large manufacturing firms in Kenya. Organization structure was found to be positively related to performance of large manufacturing firms in Kenya. Dynamic Capabilities was also found have a positive and significant influence on performance of large manufacturing firms in Kenya. On the relationship between leadership characteristics and organization performance, the study findings revealed that leadership characteristics have a positive and significant influence on performance of large manufacturing firms in Kenya. Policy recommendation: The study recommended that large manufacturing firms in Kenya should put in place better organizational structure strategies, improved information technology put in place strategies that encourage their leaders to have leadership characteristics and structural dynamic capabilities as they lead to high performance